(untitled) - Whitehead, Alfred North (New York, 1978)
Contents: Process and Reality, Whitehead's magnum opus, is one of the major philosophical works of the modern world, and an extensive body of secondary literature has developed around it.
Keywords: Cosmology,Vũ trụ học